(untitled) (Mwanga wa Lugha, 2022)
The role of music and dance in both modern and indigenous African societies cannot be overemphasized. Music and dance accompany almost every African human activity right from birth to death. Among the variety of songs that accompany musical instruments in indigenous African societies is the lyre music and dance, which is found amongst ethnic groups such as Abagusii, Kuria, Luo, Baganda and the Luhya in East Africa. Despite its significant role in the society, lyre music and dance is seen as a tool for entertainment by some scholars (Karyu, 1991 & Odenyo, 2005). This study therefore sought to investigate the role of lyre music and dance in knowledge preservation and political mitigation among the Bukusu of Kenya in the face of societal change; an area of study that has received little attention from scholars. The study employed exploratory and descriptive design, whereby data were collected through in-depth face to face interviews, focus group discussions, non- participant observation, pictorial, audio and video recording. The multimodal theory of discourse analysis (Kress, 2012) was applied in data analysis, which comprised of texts, contexts and artefacts. Findings reveal that despite the changes in society, lyre music and dance among the Bukusu still remains an important social space for knowledge preservation and political mitigation. The study recommends that the Bukusu lyre music and dance should be preserved and managed for future generations and that future research should consider other types of musical arts that are used by the Bukusu and other speech communities for knowledge preservation and mitigation of societal issues.